2017
DOI: 10.1080/1028415x.2017.1325974
|View full text |Cite
|
Sign up to set email alerts
|

Oxidative injuries induced by maternal low-protein diet in female brainstem

Abstract: Many studies have shown that a maternal low-protein diet increases the susceptibility of offspring to cardiovascular disease in later-life. Moreover, a lower incidence of cardiovascular disease in females than in males is understood to be largely due to the protective effect of high levels of estrogens throughout a woman's reproductive life. However, to our knowledge, the role of estradiol in moderating the later-life susceptibility of offspring of nutrient-deprived mothers to cardiovascular disease is not ful… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
14
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 15 publications
(14 citation statements)
references
References 48 publications
0
14
0
Order By: Relevance
“…Low-protein regimens at conception or during pregnancy bring additional evidence on the noxious epigenetics effects of maternal nutrition deficiency on the offspring health: in animal models, a protein-restricted maternal diet has been associated with impaired immune response ( 42 ), increased sensitivity to oxidative stress ( 43 ), metabolic abnormalities, and glucose dyshomeostasis ( 44 ).…”
Section: Effect Of Maternal Nutrition On Pregnancy Epigenetics and Fementioning
confidence: 99%
“…Low-protein regimens at conception or during pregnancy bring additional evidence on the noxious epigenetics effects of maternal nutrition deficiency on the offspring health: in animal models, a protein-restricted maternal diet has been associated with impaired immune response ( 42 ), increased sensitivity to oxidative stress ( 43 ), metabolic abnormalities, and glucose dyshomeostasis ( 44 ).…”
Section: Effect Of Maternal Nutrition On Pregnancy Epigenetics and Fementioning
confidence: 99%
“…In regard to oxidative balance, our data demonstrated that females are more protected from oxidative damage than male animals in brainstem, wherein the lower production of ROS gathered with a high CAT activity and elevated thiol content culminated in a compelling lower lipid peroxidation. The oxidative stress protection in female gender has been widely described in oestrogen-related neuroprotection studies due to its capacity to upregulate the expression of several antioxidant enzymes (Irwin et al, 2008;Moor et al, 2004;Yao et al, 2012), similarly to in the brainstem or brainstem nuclei (Lee, Ryu, & Lee, 2013;Pierce et al, 2009;Shih, 2009;de Sousa et al, 2017;Subramanian et al, 2011;Wang & He, 2002;Wang et al, 2008;Wu, Chen, & Shih, 2012).…”
Section: Gender Effectmentioning
confidence: 99%
“…The researchers suggest that female hormones could be relevant in the prevention of hypertension in pre‐menopausal females . In addition, hyperactivity of the rennin‐angiotensin system and augmented oxidative stress, relevant features in hypertensive condition, are not changed in female offspring exposed to maternal protein malnutrition . Please note that it is not the focus of this review to perform a comparison between genders in maternal malnutrition induced‐hypertension models.…”
Section: Historical Evidence Of Maternal Protein Restriction and Hypementioning
confidence: 99%
“…41 In addition, hyperactivity of the rennin-angiotensin system and augmented oxidative stress, relevant features in hypertensive condition, are not changed in female offspring exposed to maternal protein malnutrition. 44,45 Please note that it is not the focus of this review to perform a comparison between genders in maternal malnutrition induced-hypertension models. For better understanding of the evidence for sex differences in developmental programming of hypertension see Ojeda and colleagues (2008) 46 and Davis and colleagues (2017).…”
Section: Some Of the Initial Indications Of A Relationship Between Inmentioning
confidence: 99%